An institutional assessment of the public interest and accountability committee (PIAC) in Ghana's oil and gas sector. Issue 4 (2nd October 2019) - Graham, Emmanuel; Gyampo, Ransford Edward Van; Ackah, Ishmael; Andrews, Nathan
ABSTRACT: Ghana's Petroleum Revenue Management Act 815 (amended to Act 893 in 2015) established the Public Interest and Accountability Committee (PIAC) in 2011 with the mandate to ensure accountability and transparency in the management and usage of oil and gas revenue. This paper critically examines the activities and operations of the PIAC from 2011 vis-à-vis its legally reposed mandate. It points to severe deficit in accountability but improvements in transparency in the management of oil and gas revenues in spite of the existence and operations of the PIAC. After eight years of operation, the PIAC continues to suffer monumental challenges that undermine its effectiveness in serving as an accountability and transparency initiative in Ghana's oil and gas sector. The paper makes some recommendation based on the empirical challenges of the PIAC identified to strengthen the PIAC to deliver effectively on its mandate.